CONSEQUENCES OF THE POLICY OF TSARIST RUSSIA IN THE DEVELOPMENT OF THE NATIONAL ECONOMY OF THE KARAKALPAKS - Tangirbergenova K.; Uzakbergenov J. (Scholar Express Journal, 2022)
The colonial agrarian policy of tsarist Russia in Karakalpakstan largely led to the development of a commodity economy, but as a result of the colonial policy of tsarism, Karakalpakstan was turned into a raw material base of the Russian Empire
Keywords: history; culture; heritage; trade